Identification of Eye-Specific Domains and Their Relation to Callosal Connections in Primary Visual Cortex of Long Evans Rats - Laing, R.J. (Cereb Cortex, 2015)
Ocular dominance columns (ODCs) exist in many primates and carnivores, but it is believed that they do not exist in rodents. Using a combination of transneuronal tracing, in situ hybridization for Zif268 and electrophysiological recordings, we show that inputs from both eyes are largely segregated in the binocular region of V1 in Long Evans rats. We also show that, interposed between this binocular region and the lateral border of V1, there lies a strip of cortex that is strongly dominated by the contralateral eye. Finally, we show that callosal connections colocalize primarily with ipsilateral eye domains in the binocular region and with contralateral eye input in the lateral cortical strip, mirroring the relationship between patchy callosal connections and specific sets of ODCs described previously in the cat. Our results suggest that development of cortical modular architecture is more conserved among rodents, carnivores, and primates than previously thought.